Inclusive Islamic Education for Learners with Disabilities: Reconstructing Equitable Pedagogical Practices in Contemporary Madrasahs - Mukhlis Mukhlis; Ainul Jaria Maidin; Faruk Kerem Sentürk; Ihsan Yilmaz; Esraa Al-Sarray (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2024)
This study investigates strategies for reconstructing inclusive Islamic education to ensure equitable learning opportunities for students with disabilities in contemporary madrasahs. A qualitative library research approach was employed through a systematic analysis of literature concerning inclusive education, Islamic educational philosophy, disability studies, and educational equity. The findings indicate that Islamic teachings strongly support inclusive educational practices grounded in justice, compassion, equality, and respect for human dignity. However, challenges remain regarding teacher preparedness, curriculum adaptation, accessibility, and institutional policy. The study proposes an Inclusive Islamic Pedagogical Framework integrating universal design for learning, differentiated instruction, Islamic ethical values, and collaborative educational support systems. The novelty of this study lies in presenting a comprehensive conceptual framework that bridges Islamic educational philosophy with contemporary inclusive education principles to improve educational access and participation for learners with disabilities